Determinants of gold price in Malaysia and Singapore / Hidayah A. Rahman - A. Rahman, Hidayah (2020)
Gold, one of the precious metals in the world and it has been known as yellow metal and a valuable asset to a country because of its liquidity. The main objective of this study is to examine the determinants of gold price in Malaysia and Singapore. The selected macroeconomic variables are inflation rate, exchange rate, and crude oil price. Using several tests which is descriptive analysis, stationary test by Augmented Dickey-Fuller (ADF) test, co-relation test, regression analysis, and test on the assumption for all the data on monthly basis from January 2015 to September 2020. By adopting their empirical model, there is the existence of a relationship between selected macroeconomic variables and gold price in Malaysia and Singapore. Moreover, the results showed consistent with existing studies. This paper has contributed new evidence proven to the existing -research studies and -provides a clearer view on the gold price in Malaysian and Singapore to individuals and investors as well as government bodies in analysing the movement of the gold price.